G471(P) Back to the basics – history, history and history!. (27th April 2016) - Vanker, H; Lloyd, H; Mukherjee, A
Abstract : Aim: To emphasis the importance of history taking in diagnosing maturity onset diabetes of the young (MODY) Methods/Results: MODY accounts for around 2% of paediatric diabetic cases. Mutation in hepatocyte nuclear factor 1-beta (HNF1-β) gene is rare (accounting for approximately 6% of MODY diagnoses in the UK) and is associated with RCAD (renal cysts and diabetes) syndrome. Owing to the common clinical features of both type 1 and type 2 diabetes, the diagnosis of MODY proves to be a paediatric challenge. A 7 year old girl presented with polydipsia, polyuria and weight loss. On examination, weight was above the 99.6th centile and height on the 91st centile. There was an impaired oral glucose tolerance test, a raised HbA1C and raised plasma insulin but normal plasma C-peptide, collectively suggesting a probable diagnosis of type 2 diabetes. Follow up consultation revealed Glutamic Acid Decarboxylase (GAD) and Islet cell antibodies to be positive, changing the diagnosis to be Type 1 diabetes, most likely MODY. Subsequent detailed history taking revealed a previous left-sided nephrectomy due to congenital multicystic, dysplastic kidney. A renal ultrasound was repeated which demonstrated a cyst in the remaining kidney. Given the background of renal development disease and positive antibodies, the possible diagnosis of MODY, in particular RCAD, was postulated. Specialists at the Exeter University genetic centre echoed the high probability of this and the HNF1-β gene mutation was done. Although it subsequently came back negative, this case can still be used to raise awareness of the existence of MODY amongst our medical and nursing colleagues. Conclusion: This case highlights the fundamental importance of thorough history taking to ensure a timely diagnosis of MODY especially very rare HNF1-β mutation, to optimise both treatment and prognosis.